Dansk forskning i Dødehavsrullerne siden 1947: En forskningshistorisk skitse - Høgenhaven, Jesper (Dansk Teologisk Tidsskrift, 2022)
This article is a recapitulation of the history of research in Denmark on the Dead Sea Scrolls since their discovery. Before 1947, some authors had already treated subjects like the history of the Essenes and the Cairo Damascus Document. When news of the manuscript findings near Qumran reached the scholarly world and the Cave 1 manuscripts became known, Danish scholars showed great interest in the material, while at the same time proceeding with caution in the light of the uncertainty of the historical background of the scrolls. The available texts were translated into Danish and several studies as well as popular books were written. After a partial standstill during the 1960s and 1970s, the publication of the manuscript material especially from Cave 4 prompted an array of new investigations into the ancient Jewish worlds reflected in the scrolls. In recent years Dead Sea Scrolls scholars in Denmark, like their international colleagues, have renewed and expanded their methodological toolbox.